Addition of litter, its decomposition and nutrient release in rubber plantations in Tripura - Varghese M; Pothen J; Sharma A C (Indian Journal of Natural Rubber Research, 2001)
A study of litter fall from rubber trees, litter in standing crop and their decomposition was carried out for a period of two years at Agarthala, Tripura, North East India. Annual litter fall was estimated in a 14 year old rubber plantation of clone RRIM 600 which had a density of 317 mature rubber trees per ha. Litter samples were collected at monthly intervals from 12 traps randomly placed in an area of one ha. The total annual litter fall ranged from 6.8 to 7.8 t per ha. Leaf litter accounted for 66 per cent of the total litter and the major portion of the leaf fall occurred from January to March. There were no significant differences in litter production between two consecutive years. Maximum litter in standing crop occurred in March and it decreased progressively as the rates of decomposition increased. Nutrients ranging from 94 to 130 kg of N, 5 to 6 kg of P, 22 to 25 kg of K, 106 to 168 kg of Ca and 17 to 33 kg of Mg were returned to the soil through total litter fall. Decomposition of leaf and petiole litter was studied for a period of 360 days. After 120 days a weight loss of 16-21 per cent was observed for leaf litter, whereas a higher weight loss of 28-30 per cent was observed for petiole litter indicating faster decomposition of petioles. As the decomposition, the concentrations of K, Mg and Ca decreased markedly. Decomposition quotient (K L) for leaves ranged fom 1.97 to 2.92, for twigs from 3.24 to 3.24 to 4.06 and from 2.28 to 3.20 for petioles. The total quantity of leaf fall in the mature plantation in Tripura and the nutrient return through litter was comparable to that in the traditional rubber growing tracts.
Keywords: Decomposition; Hevea brasiliensis; Litter; Nutrient release